Application of Technical and Non-Technical Factors Affecting Safety Management Systems on the Container Ships in National Shipping - Sembiring, Honny Fiva Akira; Arafah, Willy; Ricardianto, Prasadja; Endri, Endri (Jurnal Manajemen Transportasi & Logistik (JMTRANSLOG), 2025)
This study aims to analyze the problems in implementing a Safety Management System on container ships by implementing international safety management conventions. Analysis of the relationship between technical and non-technical factors of SMS that affect maritime safety. This study uses a qualitative method using NVivo 12 software. The informants are the Captain, Officers, Chief Engineer, and Engineers, and involve Designed Person Ashore, Marine Inspector, Shipping Entrepreneurs, and Marine Academy with a total of 32 informants to obtain diverse and comprehensive perspectives on the phenomena that occur on board the ship. The sampling technique uses NVivo 12 software to produce data visualization through project maps, coding, and interpretation based on node and sub-node codes. The results of this study were obtained through a comprehensive analysis of the problems of implementing a safety management system on ships that must comply with the provisions of the International Safety Management Code and the Convention for the Safety of Life at Sea as well as factors such as crew training and human resource development, which are consistently integrated in the successful implementation of SMS and will later be used by stakeholders to improve the safety of container ships in the maritime sector.